PENGARUH KEPERCAYAAN DIRI DAN KONFORMITAS REMAJA TERHADAP PERILAKU KONSUMTIF SISWA KELAS XIDI SMK - Aryati, Agnes; Nuraini, Nuraini; Okkiana, Okkiana (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine how much confidence in Class XI students in Sintang High School SMK 20016/2017 Academic Year, how much Class XI students conformity in Sintang High School SMK 20016/2017 Academic Year, and how much the Class XI students' Consumer Behavior in Vocational High School Budi Luhur Sintang Academic Year 20016/2017. This research is a type of survey research. The source of this research data is the students of class XI of Budi Luhur Sintang Vocational School and the main data is the student questionnaire. The results of this study indicate that Class XI Student Confidence in Budi Luhur Sintang Vocational High School has a positive effect on the consumptive behavior of class XI students of Budi Luhur Sintang Vocational High School at 0.686. Keywords: Self -Confidence, Youth Conformity, Consumptive Behavior